Evaluating the feasibility and acceptability of a co-designed physical activity intervention for rural middle schoolers: a pilot study - Janette M. Watkins; Julia E. Brunnemer; Kathleen N. Heeter; Andrew M. Medellin; William C. Churchill; Janelle M. Goss; James M. Hobson; Nicole E. Werner; R. Glenn Weaver; Vanessa M. Martinez Kercher; Kyle A. Kercher (BMC, 2024)
Abstract Background Lack of physical activity is a concern for children across diverse backgrounds, particularly affecting those in rural areas who face distinct challenges compared to their urban counterparts. Community-derived interventions are needed that consider the unique context and additional physical activity barriers in under-resourced rural settings. Therefore, a prospective pre-post pilot/feasibility study of Hoosier Sport was conducted over 8-weeks with 6th and 7th grade children in a low-socioeconomic rural middle school setting. The primary objective of the present study was to assess trial- and intervention-related feasibility indicators; and the secondary objective was to collect preliminary assessment data for physical activity levels, fitness, psychological needs satisfaction, and knowledge of physical activity and nutrition among participating youth. Methods This prospective 8-week pilot/feasibility study took place in the rural Midwestern United States where twenty-four middle school students participated in a mixed-methods pre-post intervention during physical education classes. The intervention included elements like sport-based youth development, individualized goal setting, physical activity monitoring, pedometer usage, and health education. Data were collected at baseline (T1) and post-intervention (T3), with intermediate measures during the intervention (T2). Qualitative data were integrated through semi-structured interviews. Analytical methods encompassed descriptive statistics, correlations, repeated measures ANOVA, and thematic analysis. Results Key findings indicate robust feasibility, with intervention-related scores (FIM, AIM, and IAM) consistently surpassing the "good" threshold and 100% retention and recruitment success. Additionally, participants showed significant physical performance improvement, shifting from the 25th to the 50th percentile in the 6-minute walk test (p < 0.05). Autonomy and competence remained high, reflecting positive perceptions of program practicality. Nutrition knowledge, initially low, significantly improved at post-intervention (p < 0.01), highlighting the efficacy of targeted nutritional education in Hoosier Sport. Conclusions This study pioneers a community-engaged model for physical activity intervention in under-resourced rural settings. Positive participant feedback, coupled with improvements in physical fitness and psychosocial factors, highlights the potential of the co-design approach. The findings offer valuable insights and a practical template for future community-based research, signaling the promising impact of such interventions on holistic well-being. This research lays the foundation for subsequent phases of the ORBIT model, emphasizing collaborative, community-driven approaches to address the complex issue of declining physical activity levels among adolescents.